2012
DOI: 10.5114/aoms.2012.31251
|View full text |Cite
|
Sign up to set email alerts
|

Effect of TSLC1 gene on growth and apoptosis in human esophageal carcinoma Eca109 cells

Abstract: IntroductionTo explore the effect of tumor suppressor in lung cancer 1 (TSLC1) on proliferation and apoptosis in esophageal cancer Eca109 cells.Material and methodsEca109 cells were divided into three groups: TSLC1 transfected group (TTG), mock group (MG) and untransfected group (UTG). The TTG and MG were transfected transiently with the pIRES2-EGFP-TSLC1 eukaryotic expression vector and pIRES2-EGFP vector respectively. The UTG was a blank control. The TSLC1 expression in TTG was analyzed with the fluorogram a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…The cell adhesion molecule 1 (CADM1) gene, which is also known as TSLC1 or Necl-2 , has been generally investigated as a tumor-suppressor gene in various tumors, including prostate, esophageal, nasopharyngeal, non-small cell lung and cervical cancers ( 16 , 18 , 23 25 ). Many studies have shown that CADM1 , as a tumor-suppressor gene, is associated with inhibition of cell proliferation, as well as invasion and induction of apoptosis in various tumor cells, including the non-small cell lung cancer A549 cell line ( 26 ), human esophageal carcinoma Eca109 cells ( 27 ), and a hepatocellular carcinoma cell line ( 28 ). CADM1 is downregulated in many cancers, frequently via promoter hypermethylation ( 16 , 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…The cell adhesion molecule 1 (CADM1) gene, which is also known as TSLC1 or Necl-2 , has been generally investigated as a tumor-suppressor gene in various tumors, including prostate, esophageal, nasopharyngeal, non-small cell lung and cervical cancers ( 16 , 18 , 23 25 ). Many studies have shown that CADM1 , as a tumor-suppressor gene, is associated with inhibition of cell proliferation, as well as invasion and induction of apoptosis in various tumor cells, including the non-small cell lung cancer A549 cell line ( 26 ), human esophageal carcinoma Eca109 cells ( 27 ), and a hepatocellular carcinoma cell line ( 28 ). CADM1 is downregulated in many cancers, frequently via promoter hypermethylation ( 16 , 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cell Adhesion Molecule 1 is a protein that has been found to be strongly expressed in neurons, [71][72][73][74][75] spermatogenic cells, [52,[76][77][78] immune cells, [79][80][81][82][83][84][85][86][87] and endothelial cells [88,89]. Functionally, CADM1 has been shown to participate in homophilic binding, and paradoxically, tumor suppression.…”
Section: Cadm1: An Additional Role For a Versatile Protein?mentioning
confidence: 99%
“…Although important advances exist in multimodal therapy of ESCC, prognosis remains poor, with a 5-year survival rate less than 15% [ 3 ]. Therefore, identifying reliable diagnostic and prognostic biomarkers of ESCC is critical, as well as elucidating molecular mechanisms participating in esophageal carcinogenesis [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%